2017
DOI: 10.1001/jamafacial.2017.0459
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mental Health Status With Perception of Nasal Function

Abstract: IMPORTANCE Mental health issues are thought to be overrepresented among patients undergoing rhinoplasty and may be associated with patient presentation prior to surgery.OBJECTIVE To assess the association of poor mental health with perception of nasal function. DESIGN, SETTING, AND PARTICIPANTSA cross-sectional study of patients presenting for airway assessment was performed from December 1, 2011, to October 31, 2015, at 2 tertiary rhinoplasty centers in Sydney, Australia. Mental health was independently defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…While devising a management plan for those seeking rhinoplasty it is important to incorporate thorough assessment of mental health as it has lasting impact on the outcome of surgery. 13 Results of this study are consistent with other studies as majority of patients seeking rhinoplasty were young, single females. Similar results were observed in studies done by Abbas, 14 de Brito, 15 and Bouman, 16 in which there was higher prevalence of females seeking rhinoplasty as they are preoccupied with physical appearance of their breast, hip with particular focus on skin tone, color, hairs or shape of nose, 17 as compared to males who are more concerned about their body hairs, genital and height.…”
Section: Discussionsupporting
confidence: 91%
“…While devising a management plan for those seeking rhinoplasty it is important to incorporate thorough assessment of mental health as it has lasting impact on the outcome of surgery. 13 Results of this study are consistent with other studies as majority of patients seeking rhinoplasty were young, single females. Similar results were observed in studies done by Abbas, 14 de Brito, 15 and Bouman, 16 in which there was higher prevalence of females seeking rhinoplasty as they are preoccupied with physical appearance of their breast, hip with particular focus on skin tone, color, hairs or shape of nose, 17 as compared to males who are more concerned about their body hairs, genital and height.…”
Section: Discussionsupporting
confidence: 91%
“…Greater benefit was seen in NOSE scores in those with poor mental well-being, but this may be due to a bias inherent in comparing preoperative and postoperative outcomes. Indeed, preoperatively those with impairments in mental well-being report significantly worse NOSE scores than those with normal mental well-being (mean [SD] score 2.64 [0.95] vs 1.96 [1.04]; P < .001) 48 ; hence, patients with a better initial perception of nasal function have less scope for improvement following rhinoplasty. The greater improvements in perceptions of nasal function observed in individuals with poor vs normal mental well-being may thus be a consequence of a lower baseline rather than a different surgical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2017 cross-sectional study of *500 patients, it was shown that those with poor mental health had poorer scores in not only visual cosmetic scales but also functional scales including the NOSE and SNOT-22 scales, compared with mentally healthy patients with similar nasal airflow. 30 This indicates that mental health is linked to both cosmesis and function, which must be taken into consideration when evaluating patients for surgical rhinoplasty.…”
mentioning
confidence: 99%